The Effect Of Giving Red Guava Juice To Grade of Pregnant Women’s Hemoglobin - Fitri Apriyanti; Lara Andriani (Universitas Andalas, 2019)
According to the World Health Organization (WHO) in 2014, as many as 41.8% of maternal deaths in developing countries were associated with anemia in pregnancy and most were caused by iron deficiency and acute bleeding, not even the two interacting frequently. Red guava juice can increase hemoglobin levels that can treat anemia. The purpose of this study was to determine the effect of giving red guava juice (psidium guajava, linn) to hemoglobin levels.This type of research is quasi-experimental (quasi-experimental) with a non-equivalent pretest-posttest design carried out in the village of Kuok working area PUSKESMAS Kuok on July 26 -1 August 2018. The population in this study were all pregnant women who suffer from anemia with hemoglobin levels of 8-11 gr%. The research sample amounted to 15 respondents using total sampling techniques. Hemoglobin level examination use haemometer digital. The data analysis use T-test.The results of this study obtained mean hemoglobin levels before administration of red guava juice (Psidium Guajava, Linn) was 8.80, mean hemoglobin level after administration of red guava juice (Psidium Guajava, Linn) is 12.60. Hb levels before and after administration of red guava juice were 3.8. The statistical test results obtained p-value 0,000 (<0.05). Conclusion This study has the effect of giving red guava juice (Psidium Guajava, Linn) to the hemoglobin level of pregnant women.